The trainer's handbook of leadership development tools, techniques, and activities - Lawson, Karen (Pfeiffer essential resources for training and HR professionals., 2011)
"In the fast-paced global environment of the 21st century, the need for effective leaders has never been greater. This book provides a variety of tools and techniques for developing leadership competencies and characteristics. Organized according to fifty empirically based competencies and characteristics, each feature is introduced with a clear definition and a discussion of its importance and application. Featuring dozens of activities and other resources to help enhance the skills of today's leaders and high-potentials, this book is a primary resource for Training and HR professionals"--